The Effect of Toxic Leadership on Turnover with Job Satisfaction as a Mediating Variable(Case Study of Generation Z in West Java) (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to examine the impact of toxic leadership on employee turnover, with job satisfaction serving as a mediating variable, particularly among Generation Z. Currently dominating the workforce; Generation Z exhibits a high turnover rate, often driven by low job satisfaction and unsupportive leadership styles. Toxic leadership, characterized by manipulative, authoritarian behaviour and a lack of responsiveness to criticism, fosters an unhealthy work environment and diminishes employee satisfaction. This decline in job satisfaction increases employees’ intentions to leave the organization, raising turnover rates. The research employs the SEM-Lisler method to analyze the relationships between toxic leadership, job satisfaction, and turnover. The findings reveal that toxic leadership significantly and negatively affects job satisfaction and turnover. Additionally, job satisfaction mediates the relationship between toxic leadership and turnover. The study’s implications highlight the importance of addressing toxic leadership within organizations by implementing training programs focused on ethics, transparency, and empathy. These initiatives can enhance job satisfaction and reduce turnover, particularly among Generation Z employees.